Effects of journal therapy counseling with anxious pregnant women on their infants' sleep quality: a randomized controlled clinical trial - Maryam Montazeri; Mojgan Mirghafourvand; Khalil Esmaeilpour; Sakineh Mohammad-Al; Paria Amiri (BMC, 2020)
Abstract Background Sleep is especially important for infants, since it stimulates the development of neural connections in their brains. Psychological stress such as anxiety could affect sleep quality. This study investigated the effects of journal therapy counseling sessions on the infants' sleep quality based on mothers' perception (primary outcome), maternal anxiety, infants' anthropometric and developmental parameters, and the frequency of exclusive breastfeeding (secondary outcomes). Methods A total of 70 healthy women with gestational age of 28-31 weeks participated in this randomized controlled trial. The participants were randomly allocated into intervention and control groups using randomized block design. Three in-person journal therapy sessions and three telephone counseling sessions (2 between in-person sessions and 1 one month postpartum) were provided to those in the intervention group, while the control group only received routine care. The Infant Sleep Questionnaire (ISQ), Exclusive Breastfeeding Checklist, and Infant Anthropometric Parameters Checklist were completed at two and four months postpartum. The Beck Anxiety Inventory (BAI) was completed during pregnancy, at the end of the intervention, and at two and four months postpartum, and the Ages and Stages Questionnaire (ASQ) was completed at 4 months postpartum. Data were analyzed using chi-square, independent t-test, ANCOVA and repeated measure ANOVA. Results There was no significant difference between the two groups in demographic characteristics and baseline anxiety scores. The mean sleep quality score in infants two months of age (MD: -4.2; 95%CI: − 1.1 to − 7.2; P = 0.007) and four months of age (MD: -5.5; 95%CI: − 8.4 to − 2.7; P < 0.001) was significantly lower in the intervention group than that of those in the control group. Based on the repeated measure ANOVA results, the mean postpartum anxiety score of mothers in the intervention group was significantly lower than that of those in the control group (AMD: -7.7; 95%CI: − 5.5 to − 10.1; P < 0.001). There was no significant difference between the two groups regarding other outcomes including the frequency of exclusive breastfeeding, and anthropometric and developmental parameters (P > 0.05). Conclusion Journal therapy can decrease mothers' anxiety and improve the infants' sleep quality based on their perception. However, further studies are required before drawing any definitive conclusion. Trial registration number Iranian Registry of Clinical Trials (IRCT): IRCT20120718010324N45. Date of registration: August 11, 2018. URL: https://en.irct.ir/trial/33211 .